2006
DOI: 10.1021/ie050406q
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Phenol by Simultaneous Use of Gas-Phase Corona Discharge and Catalyst-Supported Mesoporous Carbon Gels

Abstract: This note reports an enhancement in the degradation of phenol in aqueous solution by simultaneous use of gas-phase corona discharge and mesoporous carbon gels supporting Ni or Co as catalyst. In this study, a direct-current corona-discharge reactor that consisted of a needle cathode placed above a water film was used. Disk-shaped carbon gel was submerged in the water film under the corona-discharge zone. The degradation rates of phenol by corona-discharge reactor without carbon gels, with plain carbon gels, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Several methods for PFOA decomposition have been reported, including ultraviolet-induced photochemical reactions [4], ultrasonic cavitation [5], 185 nm vacuum ultraviolet light [6], and sulfate radicals [7]. There are many methods for water treatment using plasmas [8][9][10][11][12][13][14][15][16][17]. We recently found that plasma generated at the gas-liquid interface can easily decompose PFOA [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Several methods for PFOA decomposition have been reported, including ultraviolet-induced photochemical reactions [4], ultrasonic cavitation [5], 185 nm vacuum ultraviolet light [6], and sulfate radicals [7]. There are many methods for water treatment using plasmas [8][9][10][11][12][13][14][15][16][17]. We recently found that plasma generated at the gas-liquid interface can easily decompose PFOA [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Several efforts to degrade phenol have been undertaken using various techniques but some important methods involve the application of electromagnetic [47,48], laser [49,50] photocatalytic [51][52][53][54], mechanochemical [55], electro-catalytic [56][57][58][59], photo-electrocatalytic [60], biodegradation [61][62][63][64][65][66][67][68][69][70][71], advanced oxidation process [72] and glow discharge plasma [73][74][75] processes. However, in the following section, various sonochemical methods, used for the degradation of phenol in aqueous solutions, would be discussed.…”
Section: Remediation Methods Of Phenolmentioning
confidence: 99%
“…26,30À32 According to our previous observations of a small corona-discharge reactor using a mesoporous carbon disk as an anode, the use of a carbon anode having a high surface area can significantly improve the purification performance in phenol degradation. 32 Another previous study revealed that using a cylindrical anode can significantly increase the energy efficiency of a corona-discharge reactor. 30 From these results, we expect that using a cylindrical anode made of carbon having a high surface area may further improve the performance of a coronadischarge reactor.…”
Section: Introductionmentioning
confidence: 99%
“…We have been making efforts to develop a water purification reactor based on corona discharge because of its high reactivity and simplicity. , According to our previous observations of a small corona-discharge reactor using a mesoporous carbon disk as an anode, the use of a carbon anode having a high surface area can significantly improve the purification performance in phenol degradation . Another previous study revealed that using a cylindrical anode can significantly increase the energy efficiency of a corona-discharge reactor .…”
Section: Introductionmentioning
confidence: 99%